Have Consumers Benefited from the Reforms in the Electricity Distribution Sector in Latin America? - Estache, Antonio; Rossi, Martin (World Bank, Washington, D.C., 2013)
The authors bring new empirical evidence on the impact of the choice of ownership and regulatory regime on firms' productivity and prices paid by consumers. They collect the evidence from a sample of electricity distribution companies in Latin America. The authors rely on estimations of labor and operation and maintenance (O&M) input requirement functions using alternative econometric approaches. Their main conclusions are: 1) Private firms perform better (approximately 30 percent) than public firms. 2) The regulatory regimes matter, so that price-cap regulated firms do better than rate-of-return regulated firms, and firms regulated under hybrid regimes have intermediate performance. 3) Private firms operating under rate of return are at most as efficient as public firms. 4) There is no clear pattern of differences in electricity prices according to the regulatory regime. 5) Final prices fell in general but the drop did not match the productivity gains, implying that the operators and the state share some of the gains in the form of rents and higher tax revenue, respectively.